P158 Outcome of inflammatory bowel disease strictures. (16th January 2018) - Schulberg, J; Wright, E; Holt, B; Sutherland, T; Hume, S; Hamilton, A; Ross, A; Kamm, M
Abstract: Background: Although strictures are the most common complication of inflammatory bowel disease their natural history is not known. Strictures reflect sites of intense active inflammation as well as fibrosis. There are very few data on whether drug therapy has any impact on their progression, but recent preliminary data suggest that anti-TNF therapy may improve stricture-related symptoms and the need for surgery. 1 We have assessed the outcomes of patients with an IBD-associated stricture. Methods: Patients diagnosed with their IBD-related first stricture between 2011 and 2016, and who had a minimum of 12 months follow-up, were identified from radiology and clinical records. Magnetic resonance enterography (MRE) scans were reviewed by a single experienced radiologist and the Magnetic Resonance Index of Activity (MaRIA) score calculated. Drug therapy and the need for endoscopic dilatation, hospitalisation, and surgery were recorded. Results: 207 patients (98% Crohn's disease, 2% ulcerative colitis) with one or more strictures were included. Median follow-up for those patients not requiring surgical intervention was 45 months. 176 (85%) had ileal or small bowel strictures and 122 (59%) had undergone previous surgery for their disease. Following diagnosis 68 (33%) required intestinal surgery and 42 (20%) underwent endoscopic stricture dilatation; the remainder had drug therapy only. The median time to surgery was 6 months. Fifty-six patients (27%) were on anti-TNF therapy at stricture diagnosis. The factors associated with increased risk for bowel surgery were hospitalisation at time of stricture diagnosis ( p = 0.006), elevated CRP ( ≥10 mg/l) ( p = 0.011), and MRE features of inflammation including T2 wall hyper-enhancement ( p = 0.02), mesenteric oedema ( p = 0.03), higher stricture specific MaRIA score ( p = 0.003), stricture length >10 cm ( p = 0.01) and proximal luminal dilatation >3 cm ( p = 0.008). Previous surgery was associated with a reduced risk of surgery ( p = 0.015). There was no difference in the need for stricture surgery between those who were on anti-TNF therapy at stricture diagnosis and those who were not ( p = 0.895). Drug therapy was changed following stricture diagnosis in only a minority, with 24 (16%) commencing anti-TNF therapy within 3 months. Conclusions: To our knowledge this is the first assessment of the outcome of IBD patients with strictures. Strictures are associated with major morbidity and the use of health-care resources. Strictures associated with active inflammation, both biochemically and on MRE imaging, have a greater risk of requiring surgery. This suggests that intense anti-inflammatory therapy, titrated to control inflammation, may improve prognosis; this now needs to be studied prospectively. Reference: 1. Bouhnik Y, Carbonnel F, et al . Efficacy of adalimumab in patients with Crohn's disease and symptomatic small bowel stricture: a multicentre, prospective, observational cohort (CREOLE) study. Gut, 2017.